Yeast product supplementation influences feeding behavior and measures of immune function in transition dairy cows - Kai Yuan; Mary Beth Muckey; Luis Mendonca; Lindsey E. Hulbert (Kansas Agricultural Experiment Station Research Reports, 2014)
Yeast supplementation has been shown to increase feed intake and production in some studies with early lactation dairy cows, but the mechanisms underlying this effect remain unknown. The objective of this study was to assess the effects of supplementing a yeast product derived from Saccharomyces cerevisiae on production, feeding behavior, and immune function in cows during the transition to lactation. When fed for 3 weeks before calving through 6 weeks after calving, supplementation altered feeding behavior as well as responsiveness to vaccination and gut immunoglobulin secretion. Results suggest that yeast products can modulate several aspects of immune function and promote the consumption of smaller, more frequent meals.; Dairy Day, 2014, Kansas State University, Manhattan, KS, 2014; Dairy Research, 2014 is known as Dairy Day, 2014
Keywords: Dairy Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-156-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1111; Transition dairy cow; Yeast; Nutrition; Immunity